Effectiveness and safety profile of chidamide as maintenance therapy for peripheral T-cell lymphoma: a multicenter real-world study - Jiang, Wenjing; Zhang, Xiyuan; Song, Wei; Xu, Hong; Wei, Changrong; Wang, Juan; Wang, Ling (Frontiers in Oncology, 2025)
ObjectivePeripheral T-cell lymphoma (PTCL) is characterized by its significant variability and complexity as malignancy. Treatment outcome is poor with conventional chemotherapy. We sought to exploring the effectiveness and safety profile of chidamide monotherapy as maintenance regimen after chemotherapy.Methods69 patients for PTCL were included in the study and chidamide was administered as maintenance therapy at a dosage of 15–30 mg twice weekly (biw). The Kaplan-Meier survival analysis was employed to evaluate overall survival (OS) and progression-free survival (PFS).ResultsThe average age of participants was 61 years (17-93). The most prevalent pathologic subtype identified was angioimmunoblastic T-cell lymphoma (AITL, 55.1%), and 43.5% (30/69) of patients were classified as intermediate or high-risk cases. Of the patients, 56.5% (n=39) underwent chidamide maintenance therapy after attaining complete response (CR). Over a median follow-up duration of 43.4 months (21.7-98.4), 47.8% of patients attained CR. The median overall survival (mOS) was not achieved, while the median progression-free survival (mPFS) stood at 54.8 months (95%CI, 21.68-72.78). 20% (6/30) of PR patients exhibited CR after chidamide. Individuals who attained CR at baseline demonstrated superior PFS compared to those in PR group. Baseline effectiveness was recognized as an independent prognostic indicator for PFS. Neutropenia was the most common hematologic TRAE, with a 20.3% rate of grade 3/4 events. Dosage modifications were required for 17 patients owing to adverse events, with no fatalities attributed to the treatment reported.ConclusionIn patients with PTCL, chidamide as a single-agent maintenance treatment demonstrates effectiveness and favorable tolerability, while the remission status prior to initiating maintenance therapy is a key factor influencing treatment outcomes. Notably, the depth of response after induction therapy alone cannot determine the long-term efficacy in PTCL. Maintenance therapy can not only bring more significant benefits to CR patients but also improve the prognosis of PR patients and reduce the risk of recurrence and progression, highlighting the core value of the “induction-maintenance” sequential model. Nevertheless, this study is exploratory, and further verification through prospective studies is still required.